2018
DOI: 10.15252/embr.201745680
|View full text |Cite
|
Sign up to set email alerts
|

Active site alanine mutations convert deubiquitinases into high‐affinity ubiquitin‐binding proteins

Abstract: A common strategy for exploring the biological roles of deubiquitinating enzymes (DUBs) in different pathways is to study the effects of replacing the wild‐type DUB with a catalytically inactive mutant in cells. We report here that a commonly studied DUB mutation, in which the catalytic cysteine is replaced with alanine, can dramatically increase the affinity of some DUBs for ubiquitin. Overexpression of these tight‐binding mutants thus has the potential to sequester cellular pools of monoubiquitin and ubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Indeed, N12A mutation of UCHL3 decreased its affinity for K27 diUb by 80 %( Supporting Information, Figure S10). Note that C95A mutation of UCHL3 was previously reported to enhance its binding to mono-Ub [29,30] (Supporting Information, Figure S11), but for K27 diUb this enhancement effect was not observed in our ITC and pull-down experiments (Supporting Information, Figure S12). However,the binding affinity of the C95A mutant to other diUb chains was found to be increased (Supporting Information, Figure S12).…”
Section: Zuschriftenmentioning
confidence: 62%
“…Indeed, N12A mutation of UCHL3 decreased its affinity for K27 diUb by 80 %( Supporting Information, Figure S10). Note that C95A mutation of UCHL3 was previously reported to enhance its binding to mono-Ub [29,30] (Supporting Information, Figure S11), but for K27 diUb this enhancement effect was not observed in our ITC and pull-down experiments (Supporting Information, Figure S12). However,the binding affinity of the C95A mutant to other diUb chains was found to be increased (Supporting Information, Figure S12).…”
Section: Zuschriftenmentioning
confidence: 62%
“…Related to this, avidity-based, high-affinity protein binders specific for free ubiquitin have been engineered that are useful as sensors for free mono-ubiquitin levels 53 . Recent work has also shown that Cys-to-Ala mutation within some DUB catalytic triads results in highaffinity ubiquitin binding that could be used similarly 54 . To analyze OtDUB for this potential, we tested mono-ubiquitin binding by ITC to OtDUB 1-177 bearing a C135A mutation, but saw only weak binding (K d = 6.3 ± 0.2 µM, n = 1.8 ± 0.04) (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Affinity might be increased, as noted above, with either modified linkers or alternative UBDs. Our designs have utilized only a few of more than 20 types of UBDs 44,45 ; moreover, other Ub binding proteins such as catalyticallyinactive DUBs might be used as components of tUBD-type fusion constructs 46 .…”
Section: Discussionmentioning
confidence: 99%